Analyzing The Coin Demonstration of The Framework of Newton’s Second Law - Küçüközer, H. A.; Küçüközer, H. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
The study aim to show that some of the examples used in teaching Newton’s First Law in textbooks, academic studies, and platforms such as YouTube are in fact examples that comply with Newton’s Second Law. For this purpose, in the physics course, an easy-to-make